Kelayakan Investasi Mesin Produksi Paku di PT X - Nugroho, Yulianto Adhy; Sutapa, I Nyoman (Jurnal Titra, 2015)
PT X produces nails and wires. In the production department, especially in nailproduction, the machineries were aged up to 20 years old. Thus the company need to re-invest new machines. There are eight types of nails to produce. The investment calculation andanalysis were conducted using payback period, NPV, and profitability index. There are two alternative for the investment. The analysis results suggested that the company shall invest a total of 28 machines with a total investment of Rp 84.000.000.000,-, or 29 machines with a total investment of Rp 87.000.000.000,-. The first alternative investment is expected to be back within 6 years and 3 months. The second alternative is expected to be back within 6 years and 4 months. This two alternative investment has a positive NPV cost above zero, as well as the probability index is obtained above 1.